Spatiotemporal of ecosystem service values response to land use/cover change based on geo-informatic Tupu – A case study in Tianjin, China - Haixiao Long; Lei Yuan; Zhenglin Yin; Xiaowei Wu (Ecological Indicators, 2023)
Revealing the spatiotemporal evolution of ecosystem service value (ESV) is a prerequisite for regional ecosystem management. This paper integrates the Geo-informatic Tupu method, the Markov transfer model, and the Barycenter model to propose an analytical method for the spatiotemporal response of ESV to land use/cover change(LUCC). Taking Tianjin as the empirical study area, we estimated its ESV and spatiotemporal transfer, rise and fall changes, and migration of the barycenter. The results showed that: (1) The land use composite index of Tianjin increased, and land use changes tended to level off throughout the study period. (2) From 2000 to 2020, ESV rose and then fell, with a total decrease of 8.03 billion RMB. (3) The change of Tupu is most dramatic in Xiqing, Binhai New Area, and Dongli, where economic and social growth is rapid. The barycenter of transfer Tupu shifts from centralized distribution to decentralized distribution around Dongli, and the ESV tends to increase to the south. (4) LUCC, NDVI, and DEM mainly drive the spatial heterogeneity of ESV in Tianjin. This research offers new insights into the spatiotemporal evolution analysis of ESV and could provide scientific references for regional ecological management and policy formulation.